Magnitude and Factors Influencing Diarrhea among Under-5 Children in Rural Areas of Chittoor, Andhra Pradesh - Ravi M Rajegowda; Ravi M Rajegowda; Bharatesh D Basti; Janakiraman Pichandi; Sindhu L; Avinash R Bharani (Medsci Publications, 2018)
Introduction: Acutediarrheal diseases constitute one of the leading cause of morbidity & mortality in children below five years of age. Assessing the prevalence of diarrhea and associated factors among children of age under five will be helpful in determining the disease burden and in planning and implementation of prevention strategies at the community level. The study was conducted with the objectives to assess the prevalence and factors associated with diarrhea among under five childrenwith diarrhea Methodology: This is across sectional study with sample size of 429. Eight villages from V.Kota and Kuppam mandals, 25 houses from each village were selected randomly. Data regarding various sociodemographic factors, environmental and behavior factors were collected. Statistical analysis was done using Chi-square test and odds ratio was calculated for various factors. Results: the prevalence of diarrhea was estimated to be 47.6% (CI 42.4 - 51.7). Factors such as education of the mother, hand washing practices, use of soap during hand washing, source of drinking water, disposal of stools were significantly associated with prevalence of diarrhea Conclusion: Awareness of factors influencing diarrhea and simple interventions can reduce the burden of the diarrheal diseases.